Impact of banana based supplementary food on the nutritional status of infants - Susan Joseph K (Department of Home Science, College of Agriculture, 1992)
A study on “Impact of banana based supplementary food on the nutritional status of the infants” was conducted among selected fifteen infants using a supplementary food based on locally available food articles like banana, sesame, horsegram and skim milk powder in the proportion of 30:20:30:20. Prior to the experiment a survey was conducted to ascertain the feasibility of introducing such supplementary food among the rural families.